Gene Polymorphism of Toll-Like Receptors in Chickenpox Patients: Observational Cohort Study - T. A. Krivolutskaya; A. N. Emelyanova; A. S. Emelyanov; Yu. A. Vitkovsky (Кубанский научный медицинский вестник, 2022)
Background. Toll-like receptors (TLR) play a key role in the innate immune system, as they are the fi rst to recognize a foreign agent and initiate the human body defense mechanism. At present, the role of toll-like receptors in predicting infectious diseases requires further investigation.Objectives. To study TLR3 (Phe412Leu), TLR9 (A2848G) and TLR9 (T1237C) polymorphisms in healthy individuals and chickenpox patientsMethods. An observational cohort study involved 201 conscripted soldiers of Caucasian race, aged between 18 and 24, who was born in) and served in Zabaykalsky Krai. All of them agreed to participate voluntarily. The main group was represented by 105 males who received treatment at a military hospital with a diagnosis of chickenpox in 2019. The control group consisted of 96 healthy conscripts. The study was carried out on the basis of Chita State Academy of Medicine, Russia, and included a physical examination, anthropometry, determination of SNP genes by PCR. Amplifi cation of TLR3 and TLR9 gene fragments was carried out by means of thermocycler BIS-М111. IBM SPSS Statistics 25.0 (International Business Machines Corporation, License No. Z125-3301-14, USA) was used for statistical processing of the results.Results. A total of 354 people were screened, 87 of them did not meet the inclusion criteria and 19 refused to participate in the study. 134 males were excluded in the process, 47 of which appeared to have an exacerbation of chronic diseases, 21 were not of Caucasian race, 64 were not born in Zabaykalsky Krai, and 2 did not meet the age criteria. Totally, the study included 201 conscripted soldiers. The study groups were established as follows: chickenpox patients (n = 105) and healthy individuals (controls, n = 96). The -412Leu allele was 1.8 times less frequent in the chickenpox group, with a frequency of 0.138, compared with 0.250 in healthy controls (Ȥ 2 = 8.11; p = 0.004). In the main group, allele -412Phe prevailed with a frequency of 0.862, whereas in the control group its frequency was 0.750 (χ2 = 8.11; p = 0.004). In patients group, the genoype Phe412Phe prevailed (75.2%), the genotype Leu412Leu was less common — 2.9% (Ȥ 2 = 7.09; p = 0.03). In the group of healthy individuals, the distribution of genotypes was as follows: Phe412Phe — 60.4%, Phe412Leu — 30.2%, Leu412Leu — 9.4% (Ȥ 2 = 7.09; ɪ = 0.03). Carriers of allele -412Phe (OR = 2.08 [CI95%: 1.25–3.47]) and genotype Phe412Phe (OR = 2.08 [CI95%: 1.14–3.80]) are more likely to develop chickenpox. The probability of developing the disease for persons having the major allele A of the genotype TLR9 (Ⱥ2848G) is 0.29 [CI95%: 0.19– 0.43], for individuals with the mutant allele G of the genotype TLR9 (Ⱥ2848G) — 3.50 [CI95%: 2.32–5.29]. The prevalence of TLR9 (T1237C) in the main group was not signifi cantly different from that in the control group (p > 0.05). The probability of developing the disease for persons having the major allele A is 0.29 [95% CI 0.19–0.43], for carriers of the mutant allele G — 3.50 [95% CI 2.32-5.29]. When analyzing SNP TLR9 (A2848G), it was found that allele G prevailed with a frequency of 0.614, and allele A — with a frequency of 0.386, which is 1.9 times less than in the control group (Ȥ 2 = 36.67; p < 0.001). In patients group, homozygotes AA were found in 9.5% of cases, heterozygotes AG — in 58.1%, the rest cases were homozygous variants GG (Ȥ 2 = 40.11; p < 0.001). In the control group, all possible genotypes with a predominance of the heterozygous genotype AG were identifi ed and comprised 47.9%. When assessing the relative risk of gene variation associations connected with the development of chickenpox, we found that the polymorphism of genes TLR9 (A2848G) AG/GG increases the risk of the development of disease caused by varicella virus in the studied category by 3.4 times, and the polymorphism TLR3 (Phe412Leu) Phe/ Phe — by 1.42 times. The ROC analysis was carried out, the area under curve was 0.77 (95% CI0.70–0.83); p < 0.001; specifi city — 0.62; sensitivity — 0.8. The developed model, being a relatively good identifi er, has satisfactory properties as a discriminator.Conclusion. Our study suggests that allele -412Phe and homozygous variant Phe412Phe of gene TLR3 (Phe412Leu), as well as allele G and homozygous variant GG of gene TLR9 (A2848G) predispose to chickenpox development. Meanwhile, the allele -412Leu of gene TLR3 (Phe412Leu), allele A, and homozygous variant AA of gene TLR9 (A2848G) reduce the probability of chickenpox development.